O podcast como fonte de informação para divulgação científica sobre mudanças climáticas na Amazônia - Correa, Ketllen Samantha de Oliveira (Brasil, 2024)
It addresses the podcast as a source of information for scientific dissemination (DC) on climate change, dealing with how the process of scientific dissemination on climate change in the Amazon occurs from the podcast information source. The general objective of the research is to analyze podcasts in the Amazon that contribute to DC on Climate Change. For this, the specific objectives are: (i) To characterize the use of the podcast as scientific dissemination (DC); (ii) To map podcasts in the North region that act as scientific disseminators; (iii) To describe the contents and formats of the scientific information disseminated in the episodes on Climate Change. As for the methodology, the research is of a basic nature, whose objectives are exploratory and descriptive, with the qualitative approach and the technical procedures applied, dealing in part with a bibliographic research on podcast as a source of information, in which a systematized investigation was made in the Information Science Database (BRAPCI) following a field research, through the podcast survey on Climate Change, of which the technique of content analysis was applied for the analysis of the episodes. In the results, 6 (six) podcasts were selected, based on the established criteria, and had a total of 7 episodes, of which it is possible to observe the contents and formats of the scientific information disseminated on Climate Change. Scientific dissemination presents discussions and valuable information to understand and know how to act in the face of the climate crisis situation, through the contents disseminated in the episodes by the podcasts on the impacts of climate change, of which it involves the sectors of society in a challenge to combat them.